1996
DOI: 10.1128/jcm.34.11.2843-2846.1996
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of IS6110-based amplification assays for Mycobacterium tuberculosis complex

Abstract: The specificity of IS6110 for the Mycobacterium tuberculosis complex has recently been questioned. We observed no cross-reaction with 27 nontuberculous mycobacteria using strand displacement-and PCR-based amplification of the nucleotide 970 to 1026 and 762 to 865 regions of IS6110. These data support use of selected regions of IS6110 as M. tuberculosis complex-specific targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Our previous study demonstrated the presence of a homologous sequence by PCR, and this was confirmed by dot blot hybridization of genomic DNA (10). Despite the hybridization data, other investigators have suggested that our results may have been due to PCR contamination (8). In this study PCR was only used to prepare probes, homology was demonstrated by Southern hybridization of genomic DNA, and a higher stringency than that of the international standard method was used, implying that the sequences have a high degree of homology for IS6110.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our previous study demonstrated the presence of a homologous sequence by PCR, and this was confirmed by dot blot hybridization of genomic DNA (10). Despite the hybridization data, other investigators have suggested that our results may have been due to PCR contamination (8). In this study PCR was only used to prepare probes, homology was demonstrated by Southern hybridization of genomic DNA, and a higher stringency than that of the international standard method was used, implying that the sequences have a high degree of homology for IS6110.…”
Section: Discussionsupporting
confidence: 81%
“…No positive results were obtained, although the amount of DNA used in the experiments was not quantified. These data suggest either that there is a lower degree of homology or that the homology that we have demonstrated does not extend to the region covered by their primers (4,8). We believe that it is more likely that mycobacteria may possess a family of IS3 sequences which are closely re-lated.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…However, this homology lies in segments outside the region amplified by the T4 and T5 primers that we use (17). Therefore, PCR using the T4 and T5 primers for the IS6110 repeat sequence is useful in differentiating Mycobacterium tuberculosis from atypical mycobacterial infection because it is not found in myobacteria other than tuberculosis (18). It makes a more rapid diagnosis of rare or atypical manifestation of tuberculosis infection than tissue culture.…”
Section: Discussionmentioning
confidence: 99%
“…Various PCR methods with different DNA targets are specific and sensitive for the rapid detection of MTB in sputum and other body fluids (Eisenach et al 1991;Salian et al 1998;Haldar et al 2007;Gopinath & Singh 2009). As the insertion sequence IS6110 is normally present in multiple copies (1-25 copies) in the MTB genome and as it is specific for the MTB complex (Hellyer et al 1996), we considered it an excellent target for the detection of MTB.…”
Section: Introductionmentioning
confidence: 99%